WHO/INRUD prescribing indicators with a focus on antibiotics utilization patterns at outpatient department of Adigrat general hospital, Tigrai, Ethiopia: a retrospective cross-sectional study - Gebretekle Gebremichael Hailesilase; Brhane Gebrehiwot Welegebrial; Mezgebe Gidey Weres; Senait Abera Gebrewahd (Antimicrobial Resistance and Infection Control)
Abstract Background The World Health Organization (WHO) defines rational use of drug as a state in which medications are received by patients appropriately according to their clinical needs and individual requirement, for adequate period and at the right cost. More than 50% of all medicines are prescribed, dispensed, or sold inappropriately worldwide. This study aimed to evaluate the prescribing patterns in Adigrat general hospital, Tigrai, Ethiopia. Methods A retrospective cross-sectional study was done to evaluate prescription patterns. A systematic random sampling technique was used to select 600 prescriptions and the prescriptions were reviewed using WHO/International Network of Rational Use of Drugs prescribing indicators. Data was collected from prescriptions dispensed from 01 March 2023 to 30 March 2024 at outpatient pharmacy of Adigrat general hospital. Data was analyzed using SPSS version 21 and a p-value < 0.05 was declared statistically significant. Results A total of 1088 medicines were prescribed in 600 prescription encounters, giving an average number of 1.8 (± 0.83) medicines per encounter. The percentage of medicines prescribed by generic name was 91.5% while 98.7% of the medicines were prescribed from essential medicine list (EML). Besides, the percentages of encounters containing at least one antibiotic and one injection were 44.5% and 7.2%, respectively. A total of 340 antibiotics were prescribed in 267 encounters. Penicillins (34.4%), macrolides (23.8%) and fluoroquinolones (17.1%) were the most prevalent antibiotics classes. The “Access” and “Watch” groups covered 54.4% and 45.6% of the total antibiotics prescribed, respectively. Being under 18 years old [Adjusted Odds Ratio (AOR): 9.830, CI: 4.062–23.786], being prescribed with three medicines (AOR: 3.247, CI: 1.571–6.708) and certain diagnosis like diseases of the respiratory system (AOR: 3.750, CI: 2.136–6.584) were significantly associated with antibiotic prescribing. Conclusion This study showed deviations of prescribing patterns from WHO standards. The percentage of prescriptions with antibiotic was far from WHO optimal value. The use of antibiotics from “Access” group was below WHO standard. The percentage of medicines prescribed by generic name and the percentage of encounters with injection also deviated from WHO standard. Antibiotics prescribing showed significantly association with age, number of medicines and certain diseases.